Effectiveness of Molnupiravir and Nirmatrelvir-Ritonavir in CKD Patients With COVID-19 - Franco Wing Tak Cheng; Vincent Ka Chun Yan; Eric Yuk Fai Wan; Celine Sze Ling Chui; Francisco Tsz Tsun Lai; Carlos King Ho Wong; Xue Li; Irene Ran Zhang; Sydney Chi Wai Tang; Ian Chi Kei Wong; Esther Wai Yin Chan (Kidney International Reports)
Introduction: Even with effective vaccines, patients with CKD have a higher risk of hospitalization and death subsequent to COVID-19 infection than those without CKD. Molnupiravir and nirmatrelvir-ritonavir have been approved for emergency use, but their effectiveness for the CKD population is still unknown. This study was conducted to determine the effectiveness of these drugs in reducing mortality and severe COVID-19 in the CKD population. Methods: This was a target trial emulation study using electronic health databases in Hong Kong. Patients with CKD aged 18 years or older who were hospitalized with COVID-19 were included. The per-protocol average treatment effect among COVID-19 oral antiviral initiators, including all-cause mortality, intensive care unit (ICU) admission, and ventilatory support within 28 days, were compared to noninitiators. Results: Antivirals have been found to lower the risk of all-cause mortality, with Molnupiravir at a hazard ratio (HR) of 0.85 (95% confidence interval [CI], 0.77 to 0.95] and nirmatrelvir-ritonavir at an HR of 0.78 [95% CI, 0.60 to 1.00]. However, they do not significantly reduce the risk of ICU admission (molnupiravir: HR, 0.88 [95% CI, 0.59 to 1.30]; nirmatrelvir-ritonavir: HR, 0.86 [95% CI, 0.56 to 1.32]) or ventilatory support (molnupiravir: HR, 1.00 [95% CI, 0.76 to 1.33]; nirmatrelvir-ritonavir: HR, 1.01 [95% CI, 0.74 to 1.37]). There was a greater risk reduction in males and those with higher Charlson Comorbidity Index (CCI). The nirmatrelvir-ritonavir trial also showed reduced risk for those who had antiviral treatment and received 3 or more vaccine doses. Conclusion: Both molnupiravir and nirmatrelvir-ritonavir reduced mortality rates for hospitalized COVID-19 patients with CKD.